Analyzing student performance in learning English for General Academic Purposes (EGAP): a comparative action research study of online and offline learning - Gufron, Gufron; Md Zamin, Ainul Azmin (Universitas Islam Negeri Syarif Hidayatullah Jakarta, Indonesia, 2024)
This study aims to examine the impact of the pandemic on student performance in Learning English for General Academic Purposes (EGAP) through a comparative analysis of the pandemic and post-pandemic periods using a Classroom Action Research (CAR) approach. The sudden shift to remote and hybrid learning during the pandemic required a transformation in education, prompting an investigation into its effects on students' English language proficiency. The research was conducted with a diverse sample of students across multiple disciplines. Quantitative and qualitative data were collected, including academic records, language proficiency tests, and observations. Results revealed significant differences in student performance between the two periods, highlighting the pandemic's impact on English learning outcomes. The study also explored various factors influencing these disparities, such as access to technology, learning environments, and adaptability to remote instruction. There is a gap in research on the long-term impact of the pandemic on EGAP performance across disciplines. The novelty of this study is its use of CAR to understand the ongoing effects and adaptive strategies in EGAP education. This research sheds light on the challenges students faced during and after the pandemic the effectiveness of remote learning methods, and provides insights for educational policymakers and practitioners. ***** Studi ini bertujuan untuk menguji dampak pandemi terhadap hasil Pembelajaran Bahasa Inggris untuk Tujuan Akademik Umum (EGAP) melalui analisis komparatif antara era selama dan pasca pandemi, dengan menerapkan pendekatan Classroom Action Research (CAR). Perubahan pembelajaran jarak jauh dan hibrida selama pandemi mengharuskan transformasi dalam pendidikan, mendorong penelitian terhadap konsekuensinya terhadap kemampuan bahasa Inggris. Penelitian ini dilakukan dengan sampel mahasiswa yang beragam dari berbagai disiplin ilmu. Data kuantitatif dan kualitatif dikumpulkan, termasuk catatan akademik, uji kemampuan bahasa, dan observasi. Hasilnya menunjukkan perbedaan yang signifikan dalam kinerja siswa antara dua periode tersebut, menunjukkan dampak yang signifikan dari pandemi terhadap hasil pembelajaran bahasa Inggris. Selain itu, penelitian ini mengeksplorasi berbagai faktor yang memengaruhi disparitas, seperti akses ke teknologi, lingkungan belajar, dan adaptabilitas terhadap instruksi jarak jauh. Gap pada penelitian ini terdapat pada dampak jangka panjang pandemi terhadap kinerja EGAP di berbagai disiplin ilmu. Sementara hal yang baru dari studi ini adalah penggunaan CAR untuk memahami efek berkelanjutan dan strategi adaptif dalam EGAP. Temuan dari penelitian ini memberikan kontribusi pada pemahaman kita tentang tantangan yang dihadapi oleh siswa selama dan setelah krisis pandemi, memberikan pemahaman tentang efektivitas metode pembelajaran jarak jauh, dan memberikan wawasan bagi pembuat kebijakan dan praktisi pendidikan untuk mengatasi krisis di masa depan.